The lost civilisation of Peru - Davidson, Nick ([United Kingdom] : BBC, 2005)
Investigates the architecture, figurative art, ritual sacrifice and fall of the ancient civilization of the Moche people of Northern Peru, whose mud-brick mounds are among the oldest and biggest man-made structures in Latin America. Archaeologists contribute
Editor, Matthew Barrett.
Narrator, Bernard Hill.
dvd format.
Keywords: Mochica Indians -- Antiquities; Mochica Indians -- Rites and ceremonies; Mochica art; Mochica Indians